Translation Strategy Analysis of Kakawin Arjuna Wiwaha (Pupuh I.6) - Herdiona Hellen Herdadian; Siti Perdi Rahayu; Tadkiroatun Musfiroh (English Department, Faculty of Humanities, Udayana University, 2026)
Ancient manuscripts are handwritten documents created in the past to record events and phenomena that occurred during those times. Translation is understood as the process of rendering a source-language text into a target-language text so that the message in the source text can be understood by readers of the target text. This study aims to analyze the translation techniques applied by Djapa (2013) in translating the content of Kakawin Arjuna Wiwāha manuscript through excerpts of pupuh contained in an article titled “Tantra dalam Kakawin Arjuna Wiwaha (Kajian Filosofi)” (2025). This study focused on analyzing the translation techniques used in pupuh I.6 and employs the 18 translation techniques identified by Molina and Albir (2002) as a theoretical framework throughout the analysis. Qualitative and descriptive methods were used in this study. Djapa (2013), in general, applied 6 translation techniques, including linguistic compression, pure borrowing, generalization, linguistic amplification, modulation, and amplification, to translate Kakawin Arjuna Wiwāha manuscript from Old Javanese into Indonesian.